Improving Communication: The Ideas of John Wallen - Chinmaya, A.; Vargo, J. W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper presents the major conceptualization of John Wallen, as they relate to interpersonal relations. Wallen advises us to be aware of three basic conditions of human existence: ( I ) Individual experience is private; (2) Each person is different; (3) People are interdependent social beings. Ignorance or denial of these conditions can produce a large interpersonal gap, which is a state characterized by inaccurate communication. Four skills are outlined which help bridge the interpersonal gap, thereby increasing communication effectiveness. The four communication skills are: paraphrasing, behaviour description, description of feelings, and perception checking. Included is a list of John Wallen's unpublished papers.